Penggunaan Python dalam Pengerjaan Induksi Matematika - Salsabila Arvi; Ikrimah Sabina Triadi; Zahra Putri; Rhamanda Ardiansyah Lubis; Fitriyani Fitriyani (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Mathematics is a science that is structured deductively and systematically. Proof in Mathematics is important because it can enable critical thinking logically, and the truth of a hypothesis can be tested. Mathematical induction is a proof method that has 2 steps, namely basis and induction. With advances in technology today, there are many applications that can make this proof easier, such as Python. This research uses quantitative and qualitative approaches to prove the effectiveness of using Python compared to manual proof. The results show that Python not only speeds up work but also minimizes errors that could occur if done manually. With this research we recommend further exploitation of mathematical induction in other programming applications.